2023
DOI: 10.1590/1806-9282.20220690
|View full text |Cite
|
Sign up to set email alerts
|

Is the length of time between endometrial scratching and embryo transfer important for pregnancy success? An observational study

Abstract: OBJECTIVE: This study sought to evaluate the influence of time (early <90 days and late >90 days) and endometrial injury on pregnancy success. METHODS: This is a retrospective study in which all infertile women who underwent at least one in vitro fertilization cycle at Clinica Gera between 2010 and 2015 were considered for inclusion. We included patients with a normal ovarian reserve and regular menses at intervals of up to 30 days. A total of 315 patient files were reviewed, and the study group was composed o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…However, the studies came to inconsistent conclusions. Several studies show an enhanced implantation rate after scratching [ 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 ], while there are also several studies that could not or barely show significant differences due to scratching [ 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 , 154 , 155 , 156 , 157 , 158 , 159 ...…”
Section: Clinical Significance In Reproductive Medicinementioning
confidence: 99%
See 1 more Smart Citation
“…However, the studies came to inconsistent conclusions. Several studies show an enhanced implantation rate after scratching [ 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 ], while there are also several studies that could not or barely show significant differences due to scratching [ 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 , 154 , 155 , 156 , 157 , 158 , 159 ...…”
Section: Clinical Significance In Reproductive Medicinementioning
confidence: 99%
“…It was shown that endometrial scratching has a timely limited effect but is not restricted to the actual cycle. Until around 90 days after intervention, an improving effect was observed [ 111 ]. However, in a study where scratching in the proliferative (65.6%), periovulatory (69.6%), or secretory (64.3%) phases were compared, no significant differences due to the timing were seen [ 165 ].…”
Section: Clinical Significance In Reproductive Medicinementioning
confidence: 99%
“…Social oocyte freezing is the retrieval of oocytes followed by cryopreservation without a medical indication, only because of women's preference for postponing childbearing until later ages 1 . The optimum age for freezing is below 35 years, and the number and quality of oocytes, the used technique, and frozen periods may influence the success of pregnancy with cryopreservatived oocytes [1][2][3] .…”
Section: Introductionmentioning
confidence: 99%